Motricity, art and corporal expression. An experience through school center visits to exhibition rooms - Antonia Irene Hernández Rodríguez; Celia Moreno Barbero (FEADEF, 2010)
In this article, we intend to go beyond the educational possibilities that a non formal context generates. Art, motricity and expression are the main features of this research. We developed an activity called «Visitas culturales» , cultural visits, in several schools in Almería, where we worked with art and corporal expression at the same time from a wide point of view. The sensations and emotions of the children played the main role, highlighting the personal identity of each one. Our main aim was using art and corporal expression as a means to discover, arousing sensations and significances in the children that, probably they went unnoticed, enlarging the knowledge, not only of themselves but also of the world that sourrounds them. We consider that it is crucial creating a series of competences in the pupils, as well as appreciating and valuing in a critical way the different cultural and artistic expressions. It is also important using them as a source of enjoyment and personal enrichment. Becoming familiar with past and present expressions, boosting the aesthetic development, the creativity, the convergent and divergent thinking to facilitates the communication as well as the enrichment of differents realities and productions connected to the world of arts and culture.